PENGARUH RISIKO TERHADAP KECENDERUNGAN PRAKTIK PERATAAN PENGHASILAN PADA BANK UMUM SYARIAH - Kustono, Alwan Sri; Lasado, Jehan Masagung (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
Income smoothing is one of the interesting issues in accounting research. These matters could be occurred because income statement is one of the important parameters that can show companys performance. Practice of income smoothing arises because there was conflict between they are who have interest with the companys financial statements. This research is underlying from the number of income smoothing studies on the bank. Islamic Bank is one of the operational banks in Indonesia. Management of this bank still able has practice of income smoothing. The aimed of this study was to examine the influenceof risk toward income smoothing tendency on Islamic bank. This study used a sample of 144 income and balance sheet monthly period statements during the January 2010 up to December 2011, from 6 Islamic banks that listed in Bank Indonesia. By using the Eckel and Kustono index, this study found indication of income smoothing on Islamic banks in Indonesia. This study did not able to support the hypothesis that developed before so it can be conclude that the risk did not affect the income smoothing tendency on Islamic banks. Keywords: Income smoothing, Risk, Islamic Bank